Synthesis, Characterization and Biological Evaluation of Some Arylazopyrazoles - Sharma, R.N.; Sharma, K.P.; Dixit, S.N. (Asian Journal of Chemistry, 2010)
1-[(N-Acetyl)2,5-dichloroanilinomalonyl]3,5-dimethyl-4-(unsubsti-tuted/substituted phenylazo) pyrazoles have been synthesised in 31-65 % yield, by the reaction of 2,4-diketo-3- (unsubstituted/ substituted phenylazo) pentane with ethyl-2-[(N-acetyl)2,5-dichloroanilido] acetohydrazide. Pyrazoles are brown and yellow colour solids, having high melting points. Identity of products has been established by elemental analysis and spectral data. Newly synthesized compounds [5a-t] have been tested for their antibacterial activity against gram positive bacteria S. albus, S. aureus and gram negative bacteria E. coli and Pseudomonas piosineus. The compound 5a, 5c, 5d, 5e, 5g and 5h show significant activity and compound 5b, 5f, 5i, 5j, 5k, 5n and 5p have shown moderate activity. The same compounds were tested for their antifungal activity against Candida albicans, Aspergillus niger and Alternaria alternata at 30 mg/mL concentration using sabouraud dextrose agar media. Compounds 5a, 5c, 5d and 5g were found to be moderately active against Candida albicans and Aspergillus niger. All the other compounds did not show significant activity against the fungi at this concentration.